Language and Literature in Research and Education an Islamic Perspective - Othman, Normala (IIUM Press, 2013)
This article is an attempt to compare the teachings of Confucius and Islam, speciï¬cally The Four Books, which are authoritative works on Confucius, and the original sources of Islam, Qurâ€™Än and Sunnah. The Four Books are the most quoted sources of Confuciusâ€™ thought, namely The Great Learning (Da Xue å¤§å¦), The Doctrine of the Mean (Zhong Yong ä¸åº¸), The Confucian Analects (Lun Yu è®º) and The Works of Mencius (Mengzi åŸå). The focus shall be on the concept of family and ï¬lial piety as found in Confucianism and Qurâ€™Än and Sunnah. Both the teachings of Confucius and Islam emphasise the importance of virtues, ties and order in the family system, for example, the husband is the head of the family and responsible for the familyâ€™s existence and security. Islam and Confucianism are both patriarchal, and the husband and men are protectors of the family and deserve much respect. Young members of the family must respect and obey the elders and vice versa. To Confucius, these virtues are the heavenly way and must be cultivated and developed accordingly as li (ç¤¼) or good manners from an early age. The young and old must be treated according to their age. Similar values are also upheld in Islam. However, there are also differences between the two approaches which shall be highlighted as well.